Emotional Dynamics and Burnout Risk among Digital Immigrant EFL Teachers Amid Curriculum Change Uncertainty - Aurel Ayu Andhani; Muhammad Amin; Mahyuni Mahyuni (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines how Digital Immigrant English as a Foreign Language (EFL) teachers experience emotions and the potential for burnout when facing uncertainty during curriculum changes. It aims to understand how they react emotionally, how uncertainty affects their teaching performance, and how it relates to burnout. Using an embedded mixed-methods approach, 32 teachers participated by completing a Likert-scale questionnaire and giving open-ended comments. The quantitative data were summarized through descriptive statistics and Spearman's rho correlation, while the qualitative answers were analyzed thematically. The results show that most teachers felt hopeful, yet many also admitted feeling anxious and frustrated due to unclear policies and heavy administrative work. Even though their confidence in teaching stayed high, their motivation and classroom practices were sometimes affected. The analysis revealed a fairly strong positive link (r = .682, p < .001) between curriculum uncertainty and burnout, with most participants reporting low to moderate emotional exhaustion. These findings highlight the need for clearer curriculum guidance and stronger institutional support to help teachers manage emotional demands during curriculum transitions.